2022
DOI: 10.1108/tqm-05-2021-0128
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance and improvement program: some considerations for central banks

Abstract: PurposeQuality Assurance and Improvement Program (QAIP) is defined as “an ongoing and periodic assessment of the entire spectrum of audit and consulting work performed by the internal audit (IA) activity”. QAIP is an important component of internal auditors’ commitment to improve internal audit (IA) quality. The pressure towards improvement is urgent for central banks, in light of the vulnerabilities of their IA functions identified by the International Monetary Fund. The authors analyse the professional stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 83 publications
1
0
0
Order By: Relevance
“…The study revealed that the combined assurance framework can serve as a warning tool for management as this will be projected in the reports, which will show them whether the implemented controls are effective or should be revised. This statement is in line with a study done by Polizzi et al (2023) which stated that combined assurance can assist solve integrating and aligning assurance processes so that senior management and audit and supervisory committees obtain a comprehensive, holistic view of the effectiveness of their organization's governance, risks, and controls to enable them to set priorities and take any necessary actions. It's also further supported by Masegare (2018) that its main goal is to support corporations to comprehend their level of assurance and where improvements should take place or to address those levels to manage organisational risks.…”
Section: Resultssupporting
confidence: 80%
“…The study revealed that the combined assurance framework can serve as a warning tool for management as this will be projected in the reports, which will show them whether the implemented controls are effective or should be revised. This statement is in line with a study done by Polizzi et al (2023) which stated that combined assurance can assist solve integrating and aligning assurance processes so that senior management and audit and supervisory committees obtain a comprehensive, holistic view of the effectiveness of their organization's governance, risks, and controls to enable them to set priorities and take any necessary actions. It's also further supported by Masegare (2018) that its main goal is to support corporations to comprehend their level of assurance and where improvements should take place or to address those levels to manage organisational risks.…”
Section: Resultssupporting
confidence: 80%
“…Academic literature related to Quality Assurance and Improvement Programs (QAIP) is relatively scarce (Polizzi et al, 2023). However, several studies have contributed to developing insights into this topic.…”
Section: Resultsmentioning
confidence: 99%
“…The success of policy objectives in business entities, which generally include price and financial stability, leads to a greater focus on improving effectiveness rather than efficiency concerns. These business entities are expected to achieve their goals, so QAIP should prioritize enhancing the effectiveness of the Internal Audit (IA) function over efficiency issues (Polizzi et al, 2023). In this context, it is also important to note that IIA Standard 1311 sets requirements for internal assessors to have adequate knowledge of IA practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] affirmed that healthcare is dependent on patient-provider collaboration and supportive surroundings. Furthermore, [28]…”
Section: The Improvement Interventionsmentioning
confidence: 99%